Foreign resources and economic growth in English speaking ECOWAS countries - Henry Agbarakwe, Ugochukwu; F. Anowor, Oluchukwu; Ikue, John (Opción, 2019)
This paper sets to determine the causality between foreign resource inflows and economic growth within the English Speaking ECOWAS using data between 1970 and 2014. The individual country unit root and panel unit root tests were carried out to test for the stationarity of the variables used as a method. The result shows that human capital development can stimulate the inflows of foreign resource in ESECOC countries and thereby accelerate economic growth.We, therefore, conclude that a foreign resources-led growth assumption holds for ESECOC countries, irrespective of the time frame of the causality.